Eating Behaviors are Different in Youth with Obesity and Severe Obesity - Gross, Amy C. (Clin Obes, 2015)
OBJECTIVE: The study purposes were to: 1) investigate eating behaviors among patients in a pediatric weight management clinical practice, and 2) compare eating behavior phenotypes between children with severe obesity and obesity. METHOD: This was a retrospective cross-sectional study using data collected during clinical encounters. Participants were included if they were 2-12 years old, had a BMI ≥95(th) percentile, and if a parent/guardian completed the Child Eating Behavior Questionnaire (CEBQ). RESULTS: Participants (n=149) were children with severe obesity (n=108) and obesity (n=41). The mean Satiety Responsiveness score was significantly lower for children with severe obesity than for children with obesity. Girls with severe obesity had significantly higher Enjoyment of Food and significantly lower Satiety Responsiveness and Slowness in Eating than girls with obesity. DISCUSSION: The findings demonstrate the potential clinical utility of the CEBQ for informing tailored treatment strategies through identifying eating behavior phenotypes.